Indonesia’s Judicial Review Regime in Comparative Perspective - Roux, Theunis (Constitutional Review, 2018)
This paper provides a comparative perspective on judicial review in Indonesia after the establishment of the Constitutional Court in 2003. It starts by retelling the well-known story of the "transformation of American law" over the first half of the last century. As narrated by Morton Horwitz, that story is about how nineteenth-century industrialisation processes destabilised the premises of "Classical Legal Thought", and then about how the legal realist movement exploited the ensuing crisis to transform the way Americans think about law and its relationship to other social systems. Mining this story for generalisable concepts, the paper argues that the establishment of strong-form judicial review necessarily draws on and, in turn, influences prevailing conceptions of legal and political authority. These conceptions vary along a continuum, in the first case, from public confidence in law's autonomy to a conception of law as deeply immersed in politics, and, in the second case, from a conception of legitimate political authority as contingent on a fairly won democratic mandate to a conception of political authority as residing in the power holder's capacity to promote important social goals, such as national security or economic prosperity. Each of these variables may change independently of the other. In certain situations, however, they may also combine to form a relatively stable judicial review regime – a hegemonic legitimating ideology in which conceptions of legal and political authority lock into and mutually support each other. The fourth section uses this conceptual framework to assess the Indonesian Constitutional Court's approach to its mandate after 2003. Under its first two chief justices, the paper notes, the Court engaged in a concerted effort to build public understanding of its legitimate role in national politics. The Court's abrupt switch between its first Chief Justice, Jimly Asshiddiqie's legalist conception of law's authority and his successor, Mohammad Mahfud's more instrumentalist conception, however, has impeded the consolidation of a determinate judicial review regime. Given the considerable threats still confronting Indonesia's democracy, this situation is worrisome. The Court urgently needs to present a coherent account of its legitimate claim to authority if it is to continue playing an effective role.